Effect of Thermochemical Treatment on the Physicochemical Properties of Fiber Hemp (Cannabis sativa L.) by-Product - Kęstutis Žiūra; Egidijus Zvicevičius; Živilė Černiauskienė; Vita Tilvikienė; Aušra Bakšinskaitė; Jurgis Pilipavičius (BioResources, 2023)
The growing demand for biomass is forcing attention toward alternative resources, including agricultural by-products such as fiber hemp (Cannabis sativa L.). Growing hemp for seed produces about 10 tons of dry matter by-products per hectare. Processing-conversion technologies used in practice change the properties of primary raw materials, give them higher added value, and prepare them for various needs. In addition to economic benefits, biochar contributes to carbon sequestration and increases the sustainability of agricultural production. This study evaluated the effect of thermochemical treatment in an oxygen-free environment on some physicochemical properties of the fiber hemp by-products of the Felina 32 variety. At a heating temperature of 700 °C, the biomass yield of biochar from stems was 28.4 ± 0.5% and from seed husks was 30.6 ± 0.6%. At that time, the carbon concentration in fiber hemp stems biochar increased 1.82 times, from 45.0 ± 2.26% to 81.9 ± 8.46%, and in seed husk biochar by 1.20 times, from 56.5 ± 11, 6% to 67.9 ± 7.47%. Furthermore, the changes in the fractional composition, density, calorific value, ash content, and ash melting characteristics that occurred during the conversion of primary raw material of fiber hemp into biochar were evaluated.